Diversity of CRISPR-Cas type II-A systems in Streptococcus anginosus - Bauer, Richard; Haider, Dorina; Grempels, Aline; Roscher, Rebecca; Mauerer, Stefanie; Spellerberg, Barbara (Frontiers in Microbiology, 2023)
Streptococcus anginosus is a commensal streptococcal species that is often associated with invasive bacterial infections. However, little is known about its molecular genetic background. Many streptococcal species, including S. anginosus, harbor CRISPR-Cas systems and a CRISPR-Cas type II-A system as well as a type II-C system have been reported for this species. To characterize the CRISPR-Cas type II systems of S. anginosus in more detail, we conducted a phylogenetic analysis of Cas9 sequences from CRISPR-Cas type II systems with a special focus on streptococci and S. anginosus. In addition, a phylogenetic analysis of S. anginosus strains based on housekeeping genes included in MLST analysis, was performed. All analyzed Cas9 sequences of S. anginosus clustered with the Cas9 sequences of CRISPR type II-A systems, including the Cas9 sequences of S. anginosus strains reported to harbor a type II-C system. The Cas9 genes of the CRISPR-Cas type II-C systems of other bacterial species separated into a different cluster. Moreover, analyzing the CRISPR loci found in S. anginosus, two distinct csn2 genes could be detected, a short form showing high similarity to the canonical form of the csn2 gene present in S. pyogenes. The second CRISPR type II locus of S. anginosus contained a longer variant of csn2 with close similarities to a csn2 gene that has previously been described in Streptococcus thermophilus. Since CRISPR-Cas type II-C systems do not contain a csn2 gene, the S. anginosus strains reported to have a CRISPR-Cas type II-C system appear to carry a variation of CRISPR-Cas type II-A harboring a long variant of csn2.